2021
DOI: 10.37341/jkf.v0i0.271
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the quality of life of Knee osteoarthritis patients at the Surakarta Orthopedic Hospital

Abstract: Background: Osteoarthritis is a chronic degenerative disease of the joints. Functional limitations experienced by people with knee osteoarthritis are related to changes in quality of life. Knee Osteoarthritis needs to be assessed as a whole which includes several domains of quality of life, namely the domains of pain, stiffness and physical function. This study was conducted to determine the correlation between pain intensity and quality of life in patients with knee osteoarthritis. Methods: a qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Beberapa faktor resiko OA diantaranya usia, genetik, obesitas, jenis kelamin, dan pekerjaan (Abramoff and Caldera, 2020). Prevalensi OA secara global meningkat sebesar 113,25% dari 247,51 juta pada tahun 1990 menjadi 527,81 juta pada tahun 2019 dan di Indonesia terjadi peningkatan sebesar 100-150% (Long et al, 2022), bahkan kasus OA diprediksi akan terus meningkat hingga tahun 2025 seiring dengan pertambahan populasi usia lanjut dan obesitas (Rachmat et al, 2021). Prevalensi OA di Indonesia cukup tinggi, yakni 15,5% pada pria dan 12,7 % pada wanita, dan 70% pasien penderita OA berusia > 65 tahun (Sananta et al, 2022).…”
Section: Pendahuluanunclassified
“…Beberapa faktor resiko OA diantaranya usia, genetik, obesitas, jenis kelamin, dan pekerjaan (Abramoff and Caldera, 2020). Prevalensi OA secara global meningkat sebesar 113,25% dari 247,51 juta pada tahun 1990 menjadi 527,81 juta pada tahun 2019 dan di Indonesia terjadi peningkatan sebesar 100-150% (Long et al, 2022), bahkan kasus OA diprediksi akan terus meningkat hingga tahun 2025 seiring dengan pertambahan populasi usia lanjut dan obesitas (Rachmat et al, 2021). Prevalensi OA di Indonesia cukup tinggi, yakni 15,5% pada pria dan 12,7 % pada wanita, dan 70% pasien penderita OA berusia > 65 tahun (Sananta et al, 2022).…”
Section: Pendahuluanunclassified
“…Osteoarthritis is one of the musculoskeletal conditions with the highest prevalence leading causes of chronic disability globally and musculoskeletal disorders (Rachmat et al, 2021). Osteoarthritis is a heterogeneous condition, causing signs and symptoms in the joints associated with reduced articular cartilage integrity.…”
Section: Introductionmentioning
confidence: 99%
“…The most commonly affected joint is the knee, followed by the hand and the hip (Long et al, 2022). A person with knee osteoarthritis finds it difficult to do daily activities due to damage to the knee's structure and its manifestations, which may affect their quality of life (Rachmat et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…OA is said to be a major health issue for the world's aging population which reduces QoL and causes a variety of issues such as disability, weariness. Also, OA may affect to the person's mental health, anxiety, sleep disturbance ,and depression in addition to that, poor treatment outcomes and increase medication, which may lead to decrease QoL (7).In 2013 for example, Berat Alkan et.al. (8) conducted a study to assess the QoL in OA patients using the Kellgren Lawrence score, and SF-36 was utilized for QoL and concluded that patients with OA have poor QoL.…”
mentioning
confidence: 99%